Management of Thyroid Cancer and Related Nodular Disease - McDougall, I. Ross (Springer London : Imprint: Springer, 2006)
Management of Thyroid Cancer and Related Nodular Disease is an authoritative, readable book covering all aspects of thyroid cancer. The text is extensively referenced and includes personal experience of 35 years working with patients with thyroid disorders, including thyroid nodules and thyroid cancer. The chapters are supplemented with many illustrations including pathology, thyroid and whole-body scans, ultrasounds and other nuclear medicine and radiological studies. Important questions that patients may ask their physicians are highlighted, indicating the topics the physician should cover. Thyroid anatomy and physiology, as well as the management of thyroid nodules are covered. There are several pathological varieties of thyroid cancer and these are reviewed with examples. A chapter about the etiology and pathogenesis of thyroid cancer covers the role of radiation and gene abnormalities. Chernobyl is referred to in this chapter as well. Management of Thyroid Cancer and Related Nodular Disease is designed for physicians, including primary care doctors, endocrinologists, nuclear medicine physicians, general and head and neck surgeons, oncologists and radiation oncologists. Others groups who will find an interest in part, or all of the book are residents, medical students, and nurse practitioners when they research a patient-related problem.